2015
DOI: 10.1038/srep18498
|View full text |Cite
|
Sign up to set email alerts
|

Color Range and Color Distribution of Healthy Human Gingiva: a Prospective Clinical Study

Abstract: The aim of this study is to compile a comprehensive database on color range and color distribution of healthy human gingiva by age, gender and ethnicity. Spectral reflection of keratinized gingiva at upper central incisors was measured by spectroradiometer and converted into CIELAB values. Lightness range (ΔL*) for all groups together was 26.8. Corresponding a* (green-red) and b* (blue-yellow) ranges (Δa* and Δb*) were 18.3 and 13.0. Significant differences (p < 0.05) were recorded by age for L* and a* coordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 16 publications
(35 reference statements)
5
63
2
1
Order By: Relevance
“…Color difference thresholds for computer‐simulated human gingiva were determined based on a recent study that included subdivision of healthy human gingiva by ethnicity, age and gender . It was found that ethnicity and age had statistically significant influence on color of gingiva.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Color difference thresholds for computer‐simulated human gingiva were determined based on a recent study that included subdivision of healthy human gingiva by ethnicity, age and gender . It was found that ethnicity and age had statistically significant influence on color of gingiva.…”
Section: Discussionmentioning
confidence: 99%
“…CIELAB color coordinates of healthy keratinized gingiva of 238 subjects (subdivided by ethnicity, age, and gender), reported in a previous study, were used to represent computer‐simulated gingiva. The color coordinate ranges of simulated gingiva were as follows: L * = 50.9 – 57.0, a * = 22.9 – 27.0, and b * = 12.5 – 15.3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly utilized color system for color assessment is the CIELAB system, which defines the color characteristics as L*, a*, and b*. [20][21][22][23][24][25][26] L* represents brightness, a* represents the red-green coordinates, and b* represents the yellow-blue coordinates. The CIELAB system can mathematically express the color difference (∆E) between the two objects.…”
Section: Introductionmentioning
confidence: 99%
“…Normal color variance on the intraoral soft tissue exists at the population level based on age and ethnicity . Furthermore, even within an individual, normal color variance exists.…”
Section: Discussionmentioning
confidence: 99%